Professional, academic and industrial development needs: a competency mapping and expert opinion review - Perera, Srinath; Pearson, John; Ekundayo, Damilola; Zhou, Lei (International Journal of Strategic Property Management, 2013)
There is a tripartite pull from academics, industry and professional bodies on the development needs of the Quantity Surveyor (QS). At best, there is scope for misunder-standings between the stakeholders as to what is being required and what is being achieved. At worst there may be actual gaps in the education and/or training being offered and some discrepancies between the levels of attainment. This research sought to review the Royal Institution of Chartered Surveyors (RICS) QS competencies and their application in the delivery of QS degree programmes. The changing development needs of QSs who satisfy the aspirations of industrial, professional and academic stakeholders were investigated through content analysis of the views of an expert forum consisting of relevant stakeholders and a series of competency mapping case studies. The study revealed that there are considerably different standards right across the RICS accredited QS programmes with respect to coverage of competencies. It is concluded that there is no standard benchmark in achieving competencies and it is open to individual interpretation. Further research in the development of a Graduate Competency Threshold Benchmark is suggested to align the disparate views of the stakeholders to accommodate changing development needs.First Publish Online: 27 Jun 2013